Thermal infrared characterization of ground targets and backgrounds - Jacobs, Pieter A. (Tutorial texts in optical engineering, 2006)
This new edition updates the technologies that deal with the characterization of the thermal infrared radiation contrast between ground targets and backgrounds. Samples have been updated to comply with the current status of technology in sensor systems and countermeasures. New topics on mine detection and polarization have been included, and the section covering multispectral camouflage of personnel has been extended. The basic principles and meteorological parameters are presented, followed by calibration procedures, signature measurements, and data analyses.